Penggunaan Model Briggs Sebagai Desain Pembelajaran Dalam Menentukan Hasil Belajar Siswa Kelas 9 Di Sekolah Yayasan Hamdi Husni Medan Pancing - Syalaisha Anaqah Fatihah (Yayasan Rahmat Islamiyah, 2023)
The purpose of this study was to explore the use of Briggs Model as an effective learning design to determine the learning outcomes of Grade 9 students in Yayasan Hamdi Husni Medan Pancing School. In the context of learning design, the use of the Briggs model can help teachers understand individual student learning preferences and needs. Teachers can design learning that suits students ' learning styles and preferences, thereby improving learning effectiveness and student learning outcomes. This study uses a quantitative approach with experimental research methods. The research sample consisted of 9th grade students at Yayasan Hamdi Husni Medan Pancing School. Data is collected through learning outcomes tests that cover various aspects of knowledge and skills relevant to the material taught. The test results were then analyzed using statistical methods to compare student performance. The results showed that the use of the Briggs Model as a learning design had a positive impact on the learning outcomes of Grade 9 students. Learning using the Briggs Model showed a significant improvement in student learning performance.